Viabilidad reproductiva en cerdas empleando inseminación artificial - Astudillo Jurado, Fernando Ismael (2023)
Every day there are more pig producers that implement Artificial Insemination (AI) as a reproductive technique on their farms, although it should be noted that they do not always have the necessary knowledge to guarantee efficiency in terms of fertility and economy. The objective of this work is to describe the reproductive efficiency of sows when using AI, for which a bibliographic analysis was carried out with scientific information with authors focused on the subject. AI is a widely used procedure, whose main purpose is to reduce production costs caused by the needs in infrastructure and operational management of the boar that is frequently used on the farm; Therefore, it is crucial to guarantee an adequate careful selection of the breeders to achieve the highest standards in fertility, fecundity and prolificacy of pig farms. Overcoming the challenges of implementing changes on the farm requires the assistance of a competent technician who trains operators in detecting females in heat, ensuring that semen application coincides with the immobility reflex for best results. Although in this study it has been possible to know that natural mounting as well as AI are beneficial techniques; However, the plus of AI makes it possible to reduce the risk of disease transmission and increase the profitability of the pig farmer, but to guarantee its success, the staff or operator of the farm must be well trained to execute the application of the seminal doses in a manner correct.